Molecular Caging of Graphene with Cyclohexane: Transfer and Electrical Transport - Belyaeva, Liubov A. (ACS Cent Sci, 2016)
[Image: see text] Transfer of large, clean, crack- and fold-free graphene sheets is a critical challenge in the field of graphene-based electronic devices. Polymers, conventionally used for transferring two-dimensional materials, irreversibly adsorb yielding a range of unwanted chemical functions and contaminations on the surface. An oil–water interface represents an ideal support for graphene. Cyclohexane, the oil phase, protects graphene from mechanical deformation and minimizes vibrations of the water surface. Remarkably, cyclohexane solidifies at 7 °C forming a plastic crystal phase molecularly conforming graphene, preventing the use of polymers, and thus drastically limiting contamination. Graphene floating at the cyclohexane/water interface exhibits improved electrical performances allowing for new possibilities of in situ, flexible sensor devices at a water interface.